Narzędzia szacowania ryzyka powrotu do przestępstwa. Niezbędny instrument postępowania wykonawczego - Kalisz, Tomasz (Wydawnictwo Uniwersytetu Wrocławskiego, 2019)
The aim of the study is to discuss the most important problems related to the assess-ment of the level of risk of recidivism, taking into account actuarial methods, psycho-metric methods, and idiographic clinical trials. The point is to show tools that are intended not only to predict criminal behavior, but also to be an indicator of effective interventions aimed at social reintegration of convicts and thus a permanent form of preventing recid-ivism. These instruments are of particular importance for controlling crimes committed under the influence of sexual preference disorders.
Keywords: Model RNR; oszacowanie ryzyka; kara kryminalna; przestępstwa seksualne